Prince Hussein Al Dasni and his sons; A study of their biography and their administrative role - Hassan, Nizar (Humanities Journal of University of Zakho, 2022)
Dasin is a very ancient term, that is given to a specific region of the country of Hakkari. the use of this name dates back to before the Islamic conquest of Kurdistan, and despite that, there is very little information about it in the sources. Prince Hussein al-Dasni is considered one of the most important and prominent in the Ottoman era who was mentioned in many books and sources but most of the information about this prince was taken from the Sharafname book of the prince Sharafkhan Al-Badlisi, so we do not see any significant addition information by these sources. This research will concentrate mostly on Prince Hussein Beg Al-Dasni and his son’s roles in politics and administration, as well as, the importance of prince Hussein’s family in the Ottoman Empire. This information is obtained from contemporary documents and original Ottoman sources, in addition to that, some of this information is new and will be published for the first time.